Evaluasi Tata Kelola TI Sistem Informasi Kepegawaian (SIMPEG) Pada Instansi XYZ Menggunakan COBIT 2019 - Islamiah, Raudah; Ryanda, Nayla Husna; Megawati (Journal Informatics Nivedita, 2025)
This study discusses the evaluation of the governance of the Personnel Information System (SIMPEG) in XYZ Agencies using the COBIT 2019 approach, focusing on the MEA03 and MEA04 domains. The main purpose of this study is to assess the extent to which the personnel system is in accordance with the applicable information technology governance principles and identify aspects that still need improvement. The approach used is a mixed method through the distribution of questionnaires and interviews to employees who play a direct role in the management and supervision of the system. The assessment was carried out based on the 2019 COBIT capability level model and was strengthened by responsibility mapping using the RACI Chart. The results showed that the MEA03 domain was at a level 3 capability level (Established), while the MEA04 domain had reached level 4 (Predictable). Some weaknesses were found in the aspects of documentation, consistency of implementation, and coordination between units that were not fully optimal. In addition, the involvement of leaders still needs to be strengthened so that the evaluation and supervision process runs more effectively. Based on these findings, this study recommends improving governance policies, routine training, and strengthening the capacity of human resources as sustainable steps to improve the effectiveness and efficiency of IT governance systems in local government environments.